PENGARUH GAYA KEPEMIMPINAN, KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. FARMSCO FEED INDONESIA - Indah Lestari; Kiki Hermawan (The Asia Pacific Journal Of Management Studies, 2021)
Human resources are an important factor in achieving goals for the company. Good human resource management can be seen from the performance level of these employees. Many factors influence employee performance in a company, including leadership style, job satisfaction and work motivation. This study aims to determine whether there is an influence of leadership style, job satisfaction and work motivation together on employee performance at PT. Farmsco Feed Indonesia. This research was conducted using quantitative methods. The population in this study were all employees at PT. Farmsco Feed Indonesia, amounting to 1270 people. The research sample is a number of population members whose collection uses a random sampling technique whose number is determined to be 93 people using the Slovin formula. Data analysis using descriptive-inferential analysis. The results showed that: (1) there was a very significant influence on the leadership style variable on employee performance (2) there is a very significant influence of the Job Satisfaction variable on Employee Performance (3) there is a very significant influence on the work motivation variable on employee performance (4) there is a very significant influence on the variable Leadership Style, Job Satisfaction, and Work Motivation simultaneously (jointly) on Employee Performance.